Amyloid‐beta (Aβ1–42)‐induced paralysis in Caenorhabditis elegans is inhibited by the polyphenol quercetin through activation of protein degradation pathways. Issue 10 (28th July 2014) - Regitz, Charlotte; Marie Dußling, Lisa; Wenzel, Uwe
<x xml:space="preserve">Abstract</x> Scope Dietary polyphenols are suggested to play a role in the prevention of Alzheimer's disease, of which accumulation of aggregated beta amyloid (Aβ) is a key histopathological hallmark. We used the transgenic Caenorhabditis elegans strain CL2006, which expresses human Aβ1–42 under control of a muscle‐specific promoter and responds to Aβ1–42 aggregation with paralysis, to test effects of the polyphenol quercetin on the phenotype. Methods and results Quercetin dose‐dependently decreased the amount of aggregated proteins in solution and also paralysis in CL2006. The knockdown of key components of unfolded protein response in mitochondria or the endoplasmic reticulum by RNA‐interference (RNAi) enhanced paralysis in CL2006 but did not prevent the paralysis reducing activities of quercetin. RNAi for essential members of proteasomal protein degradation or macroautophagy also significantly increased paralysis but prevented quercetin from being effective. Quercetin increased proteasomal activity and, moreover, enhanced the flow of proteins through the macroautophagy pathway as reflected by reduced lysosome staining. Conclusion The proteostasis network, including unfolded protein response, defines the aggregation of Aβ1–42 and the associated paralysis phenotype in a nematode model for Alzheimer's disease. The polyphenol quercetin, by specifically activating macroautophagy and proteasomal degradation pathways, proved able to prevent Aβ1–42 agregation and paralysis.